Efficiency of application and need for the growth regulators ‘Tsirkon’, ‘Epin-Extra’ and micronutrient fertilizers in the cultivation of grain crops - T. G. Borisova (Зерновое хозяйство России)
The work presents an analytical review of experimental data, obtained in RSAU-MAA after K.A. Timiryazev, Omsk SAU, Orenburg SAU, Penza SAA, Kostanay RIA in 2009-2015. There have been summarized the results of long-term researches of the effect of ‘Tsirkon’, ‘Epin-Extra’, ‘Tsitovit’ and ‘Siliplant’ on grain crops under various soil-climatic conditions of RF and the Republic of Kazakhstan. The prospects of application of a new organic-mineral fertilizer ‘EcoFus’ have been considered in the paper. The top-dressing of spring wheat in the tillering stage with ‘EcoFus’ (2 l/ha) produced the increase of its productivity on 16.8% (0.72 t/ha) and nature weight on 14-17 g/l in comparison with the control. Due to the efficiency of the fertilizers a scheme of their complex application has been suggested. The patented technology allows using the tax mixtures with a reduced amount of pesticides (on 20-30%) together with ‘Siliplant’ for seedbed treatment of seeds and in the tillering stage under the threat of lodging, or together with the mixture of ‘Epin-Extra’ and ‘EcoFus’ or ‘Tsitovit’ under excessive moisture and with the mixture of ‘Tsirkon’ and ‘Tsitovit’ in the tillering stage to increase the productivity of crops on 11-25% (0.15-0.7 t/ha), to reduce costs, to improve grain quality and ecologic safety of products. In particular, triple application of ‘Siliplant’ (0.06 l/t; 1.5 l/t) for seed treatment raised productivity of the barley variety ‘Omsky golozerny 1’ in the tillering and earing stages on 0.74 t/ha, increased net income on 5.48 th rubles and enlarged profitability on 39.2% in comparison with the control